KEDUDUKAN JAMINAN FIDUSIA SETELAH ADANYA PUTUSAN PAILIT DITINJAU DARI UNDANG-UNDANG NO. 37 TAHUN 2004 TENTANG KEPAILITAN DAN PKPU - tommy leonard (jurnal.unprimdn.ac.id, 2019)
Increased economic development activities lead to the increases need for funding. Some business activities can finance its business activities through its own budget, and some do not have enough funds to finance it that they require funding from other parties. To maintain the smooth return of these funds, there must be a guarantee if in the future the debtor experiences bankrupt and break promises then the lender can hold and sell the collateral. In Article 1 Paragraph 1, UUJF is security rights over objects moving either tangible or intangible and immovable particular building can not be encumbered encumbrance. UUK-PKPU Article 1 (1) which states that: